Widowisko sportowe w kategoriach wartości fair play w ocenie zawodniczek i zawodników zespołowych gier sportowych - Bodasińska, Anna; Bodasiński, Sławomir; Piech, Krzysztof (Pedagogiczny wymiar kultury fizycznej i zdrowotnej w życiu współczesnego człowieka, 2016)
Fair play rules in sport events are based on four basic components. The scope of their action includes essential duties concerning the respect to the rules of the game and respect to the accepted behaviours and moral principles. The aim of this study was to assess the level of knowledge and awareness of competitors of team games in the scope of perceiving the components of the fair play rules in sport events. In this study a method of the diagnostic survey with using the questionnaire form and written examined statements was applied. Examination was made in 2015 and 20 volleyball players and 19 handball players took part in it. The nature of the fair play rule is not a new element for the examined players. Competitors, in most cases, have knowledge how to behave in accordance with fair game. Although this principle, unfortunately, is understood by them exclusively in categories of sports rivalry on the court or a sports hall. Attitudes to fair play components in the sport event are at the average level in the clear majority (about 89%). Choices presenting attitude, which is on the highest level, were noticed only in about 7% of respondents and the lowest level was registered at about 4% of the examined. The fair play component which was noticed on the highest level was “health”, and the lowest value was presented by: “equality of opportunity” and “respecting the principles and rules of the game”. Presented results show the high rate of the problem, both in the public and pedagogic aspect.